Exploring English language teaching - Hall, Graham (Routledge, 2011)
Includes bibliographical references and index; Theme 1: classroom interaction and management : The language classroom: roles, relationships and interactions -- Intervening in the language classroom: classroom management, interaction and learning opportunities -- The language classroom in theory and practice: complex, diverse and local -- Theme 2: Method, postmethod and methodology : Language, language learning and method: dilemmas and practices -- Language teaching methods: perspectives and possibilities -- theoretical insights for a postmethod era -- Theme 3: Learners : Focus on the language learner: individual attributes and attitudes -- Learner diversity and development: considerations for the language classroom...and beyond -- Images of language learners: from individual to social, and universal to specific -- Theme 4 : Institutional frameworks and social contexts : From global trends to local contexts: language dilemmas in the ELT classroom -- Planning and organising L2 learning and teaching: contexts and curriculum, possibilities and realities -- ELT in the world: education and politics, contexts and goals